Prevalence of type and etiology of lung cancer among the patients presented to a tertiary care hospital at central Kerala: a descriptive study - Thomas, Vadakkan Devassy; Jose, Binila; Rennis, Davis Kizhakkepeedika (International Journal of Research in Medical Sciences, 2018)
Background: Lung cancer remains the most common cause of premature mortality in men in developing countries. This study was aimed to evaluate the type and etiological factors of lung cancer in patients presented to a tertiary care hospital of central Kerala. Methods: A retrospective descriptive study was conducted in patients who were diagnosed as lung cancer. The medical records of such patients were reviewed. The data such as age, gender, etiological risk factors and type of lung cancer were collected. Patients with incomplete reports or repeated tests, or histopathological findings were negative for lung cancers were excluded from the study. Results: Total 228 patients were included in the study with age of 64.71± 9.75. The male (198) and female (30) ratio was 6.6:1, indicated the male dominance. Among the histological types, the squamous cell carcinoma was 29% (68/228) found as the most prevalent type which is followed by adenocarcinoma 26 % (61/228). The right side (132/228) lobe was the major segment than the left side (91/228). Similarly, incidence in the central region (128/228) was more than the peripheral region (69/228). Among the right side, the upper lobe was dominant when compared to the lower or middle lobe. The lower left lobe incidence was found in 47/228 cases. Among the total, 188 cases were tobacco smokers while the remaining were nonsmokers. Conclusions: Squamous cell carcinoma with right side upper lobe of lung was prevalent among the lung cancer cases. Tobacco smoking was found to be the major etiological factor.